Therapeutic interpersonal relationship through graphic expression with patients taken into a general hospital: synchrony in oral and non-oral communication - Valladares, Ana Cláudia Afonso; Furegato, Antônia Regina Ferreira; Carvalho, Ana Maria Pimenta; Scatena, Maria Cecília Morais; Silva, Ana Elisa Bauer de Camargo (Rev Rene, 2004)
Therapeutic interpersonal relationship is the contact between two people (nurse and client) acting in a systematic and planned way, through which the nurse has the chance to help the other person (the client) to talk about his feeling and thoughts, related to the situation of being sick, in order to make things clear and find ways to solve difficulties. In the present work we will present two cases in which such relationship was involved. It was carried out in a general hospital, with a child and an adult in treatment. As a mediator of the personal meetings we used drawing. The meetings were recorded and analyzed searching for synchrony between verbal and non-verbal communication. Drawing was an important resource that allowed us to explore the clients’ feelings about their condition.